Fieldnotes from a Ukrainian Culture and Gastronomy Festival, 5 May 2022, Prague - Krasnozhon, Anastasiia (Lidé města, 2022)
These ethnographic fieldnotes focus on the place, sounds, and people of the Festival of Ukrainian Culture and Gastronomy at Prague Market (Pražská tržnice), in Prague, Czech Republic, on 5 May 2022, during the fullscale war in Ukraine. The observation reveals how the topic of war impacts thecultural and self identification of Ukrainians abroad, and how it affects social interactions inside and outside the group. The fieldnotes provide a panorama of multiple interpretations and productions of the Prague Market space and provides an opportunity to observe the ongoing process of the collective memory being generated through music.